IMPLEMENTASI KEBIJAKAN MAL PELAYANAN PUBLIK (MPP) DALAM MENINGKATKAN SINERGISITAS LINTAS SEKTOR PADA DPMPTSP KABUPATEN MIMIKA - Murafer, Yantho; Saa, Septinus; Maniagasi, Yusuf Gabriel; Tambaip, Beatus; Sapioper, Hiskia C M; Renyaan, Dorthea (Universitas Cenderawasih, 2026)
This study aims to analyze the implementation of the Public Service Mall (Mal Pelayanan Publik - MPP) policy in enhancing cross-sectoral synergy at the Investment and One-Stop Integrated Services Agency (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu - DPMPTSP) of Mimika Regency, and to identify supporting and inhibiting factors in its implementation. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observation, and documentation, with informants from government apparatus and related parties in the organization of the MPP. Data analysis used an interactive model which included data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of the MPP policy in Mimika Regency has not yet reached its optimal level in encouraging cross-sectoral synergy. This is influenced by four main dimensions according to George C. Edward III's policy implementation theory, namely ineffective communication between agencies, limited resources in terms of both human resources and digital infrastructure, uneven disposition or commitment of implementers, and a bureaucratic structure that remains sectoral. Supporting factors for policy implementation include clear regulations, commitment from the local government, and the existence of the MPP as an integrated public service innovation. Meanwhile, inhibiting factors include weak cross-sectoral coordination, lack of digital system integration, limited human resource capacity, and low levels of public satisfaction with the services. Therefore, strengthening coordination, improving human resource capacity, and developing an integrated digital system are necessary to enhance the effectiveness of MPP policy implementation.